A new species of the greeneye genus Chlorophthalmus (Teleostei: Chlorophthalmidae) from the central North Pacific - Fujiwara, Kyoji; Wada, Hidetoshi; Motomura, Hiroyuki (Zootaxa, 2019)
Chlorophthalmus imperator sp. nov. (Teleostei: Chlorophthalmidae) is described on the basis of nine specimens (98.1–174.8 mm SL) from the Emperor Seamount Chain in the central North Pacific. The new species is characterized by the following combination of characters: 49–51 lateral-line scales; 6 scale rows above lateral line; 3 + 19–22 = 22–25 (modally 22) gill rakers; outermost tooth patches of lower jaw with 6–14 large thorn-shaped teeth, the tips projecting in advance of lower-jaw profile; lower-jaw symphysis with two distinct moderately-sized projections; tongue without teeth; pelvic-fin origin vertically below 4th or 5th (usually 5th) dorsal-fin ray base; head length 26.7–28.9 (mean 27.7) % SL; snout length 6.9–7.7 (7.3) % SL; horizontal orbit diameter 11.9–12.9 (12.3) % SL; upper-jaw length 11.7–13.2 (12.6) % SL; maxillary depth 3.1–3.8 (3.4) % SL; pre-dorsal-fin length 34.2–36.6 (35.3) % SL; pre-pectoral-fin length 27.3–29.8 (27.9) % SL; anus to anal-fin origin length 27.3–29.9 (28.5) % SL; pectoral-fin length 21.0–24.9 (22.7) % SL.